Using comparative genomics to uncover new kinds of protein‐based metabolic organelles in bacteria. (4th January 2013) - Jorda, Julien; Lopez, David; Wheatley, Nicole M.; Yeates, Todd O.
Abstract: Bacterial microcompartment (MCP) organelles are cytosolic, polyhedral structures consisting of a thin protein shell and a series of encapsulated, sequentially acting enzymes. To date, different microcompartments carrying out three distinct types of metabolic processes have been characterized experimentally in various bacteria. In the present work, we use comparative genomics to explore the existence of yet uncharacterized microcompartments encapsulating a broader set of metabolic pathways. A clustering approach was used to group together enzymes that show a strong tendency to be encoded in chromosomal proximity to each other while also being near genes for microcompartment shell proteins. The results uncover new types of putative microcompartments, including one that appears to encapsulate B12 ‐independent, glycyl radical‐based degradation of 1, 2‐propanediol, and another potentially involved in amino alcohol metabolism in mycobacteria. Preliminary experiments show that an unusual shell protein encoded within the glycyl radical‐based microcompartment binds an iron‐sulfur cluster, hinting at complex mechanisms in this uncharacterized system. In addition, an examination of the computed microcompartment clusters suggests the existence of specific functional variations within certain types of MCPs, including the alpha carboxysome and the glycyl radical‐based microcompartment. The findings lead to a deeper understanding of bacterial microcompartments and the pathways they sequester.